Crystal structure of Helicobacter pylori MinE, a cell division topological specificity factor - Kang, Gil Bu; Song, Hye-Eun; Kim, Mun-Kyoung; Youn, Hyung-Seop; Lee, Jung-Gyu; An, June Yop; Chun, Jang-Soo; Jeon, Hyesung; Eom, Soo Hyun (WILEY, 2010)
P>In Gram-negative bacteria, proper placement of the FtsZ ring, mediated by nucleoid occlusion and the activities of the dynamic oscillating Min proteins MinC, MinD and MinE, is required for correct positioning of the cell division septum. MinE is a topological specificity factor that counters the activity of MinCD division inhibitor at the mid-cell division site. Its structure consists of an anti-MinCD domain and a topology specificity domain (TSD). Previous NMR analysis of truncated Escherichia coli MinE showed that the TSD domain contains a long alpha-helix and two anti-parallel beta-strands, which mediate formation of a homodimeric alpha/beta structure. Here we report the crystal structure of full-length Helicobacter pylori MinE and redefine its TSD based on that structure. The N-terminal region of the TSD (residues 19-26), previously defined as part of the anti-MinCD domain, forms a beta-strand (beta A) and participates in TSD folding. In addition, H. pylori MinE forms a dimer through the interaction of anti-parallel beta A-strands. Moreover, we observed serial dimer-dimer interactions within the crystal packing, resulting in the formation of a multimeric structure. We therefore redefine the functional domain of MinE and propose that a multimeric filamentous structure is formed through anti-parallel beta-strand interactions.
Keywords: ESCHERICHIA-COLI; PROPER PLACEMENT; REGULATOR MINE; SITE; ATPASE; LOCALIZATION; OSCILLATION; PROTEIN; RING; STIMULATION